Synergistic effect of myocardial injury and mid-regional proAdrenomedullin elevation in determining clinical outcomes of SARS-CoV-2 patients - Spoto, Silvia; Mangiacapra, Fabio; D’Avanzo, Giorgio; Lemme, Daniela; Bustos Guillén, César; Abbate, Antonio; Markley, John Daniel; Sambuco, Federica; Markley, Roshanak; Fogolari, Marta; Locorriere, Luciana; Lupoi, Domenica Marika; et al. (Frontiers in Medicine, 2022)
Objective: COVID-19 is a systemic disease induced by SARS-CoV-2 causing Myocardial injury. Up to date there are few data on the correlation between Mid-Regional proAdrenomedullin (MR-proADM) and myocardial injury. The aim of this study was to evaluate whether the association of myocardial injury and elevated Mid-Regional proAdrenomedullin values could predict mortality of SARS-CoV-2 patients, to offer best management to COVID-19 patients. Methods: All patients hospitalized for SARS-CoV-2 infection at COVID-19 Center of the Campus Bio-Medico of Rome University, were included between October 2020 and March 2021 and were retrospectively analyzed. Myocardial injury was defined as rise and/or fall of cardiac hs Troponin I values with at least one value above the 99th percentile of the upper reference limit (≥ 15.6 ng/L in women and ≥ 34.2 ng/L in men). Primary outcome was 30-day mortality. Secondary outcomes were the comparison of MR-proADM, CRP, ferritin, and PCT as diagnostic and prognostic biomarkers of myocardial injury. Additionally, we analysed the development of ARDS, need for ICU transfer and length of stay (LOS). Results: A total of 161 patients were included in this study. Of these, 58 (36.0%) presented myocardial injury at admission. A MR‐proADM value ≥1.19 nmol/L was defined as the optimal cut-off to identify patients with myocardial injury (sensitivity 81.0%, specificity 73.5%). A total of 121 patients (75.2%) developed ARDS, which was significantly more frequent among patients with myocardial injury (86.2% vs 68.9%, p=0.015). The overall 30-day mortality was 21%. Patients with myocardial injury presented a significantly higher mortality compared to those without (46.6% vs 6.8%, p<0.001). When dividing the entire study population in four groups based on the presence of myocardial injury and MR-proADM values, those patients with both myocardial injury and MR-proADM ≥ 1.19 nmol/L presented the highest mortality (53.2%, p <0.001). The combination of myocardial injury and MR-proADM values ≥ 1.19 nmol/L was an independent predictor of death (OR 7.82, 95% CI 2.87-21.30; p < 0.001). Conclusion: The study is focused on the correlation between myocardial injury and MR-proADM. Myocardial injury induced by SARS-COV-2 is strongly associated with high MR-proADM values and mortality.